Evaluation of soil erosion in the Harerge region of Ethiopia using soil loss models, rainfall simulation and field trials - Claassens, A.S. (Andries Stephanus), 1943- (University of Pretoria, 2013)
Thesis (PhD (Soil Science))--University of Pretoria, 2004.